Simulation-based evaluation of upper limb postures across range of motion through muscle activity and energy expenditure - Abd Aziz, Azizul Rahman (2019)
Ergonomics assessments is an indexing approach to human work activities embrace postures, load and repetitions. There are studies on ergonomics assessments comparison which have criticized the agreement among the outputs of the assessment. This research rises from an investigation by Fountain L.J. in 2003 regarding testing on 3 different postures scored by Rapid Upper Limb Assessment (RULA) on muscles activity and claimed that it was insignificant difference between measured electromyography with RULA scores. The objective of this research is to evaluate muscles activity and energy expenditure across postures deflection differences with Malaysian male anthropometry subject concerned. This evaluation covers upper limb postures as stated by RULA section A. The research was initiated with a verification study on three different elbow flexion posture angles with different scores by RULA on the prime mover muscles activity and total energy expenditure. The result has identified that variables changes existence between different postures tested and has permit for advance detail simulation using Universiti Putra Malaysia AnyBody Modelling System (AMS) software with more angles precision within the postures range of motion. The simulation outputs concerned were the specific postures prime mover muscles activity, maximum muscles activity and potential energy. The prime mover muscles simulation result has shown the co-contraction rhythm between the agonist and antagonist muscles. Maximum muscles activity represents the maximum muscles stress and potential energy expenditure as the fatigue tendency of specific posture. Both outputs were analyzed about the statistical significance using the P-value with 0.05 cut-off. Only the potential energy expenditure variable gives a P-value lower than 0.05 for all postures tested. The relationship model between the potential energy and the angle deflected has been developed to differentiate specific postures angles fatigue tendency. Both variables output value also deviated into low, medium and high magnitudes within the range. These results have enlightened the postures risk index by kinesiology magnitude reference with scores by RULA. Besides that, maximum muscles activity is more applicable for postures stress measurement compared to prime mover muscles activity which only measures the stress on specific muscles.